2016
DOI: 10.1016/j.biopsycho.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Attachment status and mother–preschooler parasympathetic response to the strange situation procedure

Abstract: Background Early attachment relationships are important for children’s development of behavioral and physiological regulation strategies. Parasympathetic nervous system activity, indexed by respiratory sinus arrhythmia (RSA), is a key indicator of self-regulation, with links to numerous developmental outcomes. Attachment-related changes in and associations between mother and child RSA during the Strange Situation procedure (SSP) can elucidate individual differences in physiological response to stress that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 95 publications
(127 reference statements)
2
42
1
Order By: Relevance
“…Yet, the strength and direction of RSA synchrony vary by context and, in turn, such synchrony may not be beneficial in all contexts. Of note, the majority of literature on parent–child synchrony in vagal responsiveness has focused on the preschool period (e.g., Creaven et al, ; Lunkenheimer et al, ; Smith, Woodhouse, Clark, & Skowron, ), with one identified study involving school‐age youth (Woody et al, ) and one relying on an adolescent sample (Amole et al, ). Thus, further research beyond the preschool period is needed to allow for developmental comparisons.…”
Section: Biological Systems Used To Measure Parent–child Physiologicamentioning
confidence: 99%
“…Yet, the strength and direction of RSA synchrony vary by context and, in turn, such synchrony may not be beneficial in all contexts. Of note, the majority of literature on parent–child synchrony in vagal responsiveness has focused on the preschool period (e.g., Creaven et al, ; Lunkenheimer et al, ; Smith, Woodhouse, Clark, & Skowron, ), with one identified study involving school‐age youth (Woody et al, ) and one relying on an adolescent sample (Amole et al, ). Thus, further research beyond the preschool period is needed to allow for developmental comparisons.…”
Section: Biological Systems Used To Measure Parent–child Physiologicamentioning
confidence: 99%
“…positive social engagement that uses the mother as a secure base) was related to higher RSA (Bazhenova, Plonskaia, & Porges, ; Skowron et al, ). However, the literature linking attachment style to parasympathetic reactions to stressors is mixed (e.g., Smith, Woudhouse, Clark & Skowron, ), potentially because this association may be dependent on developmental stage and/or the presence or absence of incentives to regulate emotions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Smith et al. () found that secure preschool children had RSA that remained steady across the strange situation; avoidant children's RSA increased during the first separation, whereas ambivalent children's RSA decreased across the strange situation. Smith et al.…”
Section: The Present Studymentioning
confidence: 99%
“…Smith et al. () suggested that these RSA patterns may reflect the emotional and behavioral regulation strategies associated with each of the attachment classifications. For example, the pattern of high RSA (vagal augmentation) found in the avoidant children may reflect use of PNS activation to cope with stressors, consistent with the deactivating strategies of insecure–avoidant children.…”
Section: The Present Studymentioning
confidence: 99%